Digitalization of Business Profile to Promote Qualified Marketing System of SMEs’ Product - RR.Siti Muslikhah; Maisaroh; Tri Lestari Wahyuning Utami; Khoirina Noor Anindya; Mellisa Fitri Andriyani Muzakir (Asian Journal of Community Services, 2023)
This community service program is a collaboration between the team and the Aisyiah Sleman Entrepreneurs Association (IPAS) in Yogyakarta. IPAS members are SMEs such as culinary, handicraft, batik, convection, etc. IPAS marketing is still limited in local circles, so it has not been able to reach a wider market. The obstacles are lack of knowledge and skills in marketing products and the unfamiliarity of their business in the community. For this reason, SMEs need a business profile that can provide information on the products offered can increase brand awareness and build relationships with customers. This service focused on digitizing IPAS's business profile. The result is IPAS members who already have a digital business profile, for example, Google My Business.